UNC5D, suppressed by promoter hypermethylation, inhibits cell metastasis by activating death‐associated protein kinase 1 in prostate cancer. Issue 4 (20th February 2019) - Dong, Dong; Zhang, Lufang; Bai, Changsen; Ma, Na; Ji, Wei; Jia, Li; Zhang, Aimin; Zhang, Pengyu; Ren, Li; Zhou, Yunli
Abstract : Prostate cancer (PCa) death primarily occurs due to metastasis of the cells, but little is known about the underlying molecular mechanisms. This study aimed to evaluate the expression of UNC5D, a newly identified tumor suppressor gene, analyze its epigenetic alterations, and elucidate its functional relevance to PCa metastasis. Meta‐analysis of publicly available microarray datasets revealed that UNC5D expression was frequently downregulated in PCa tissues and inversely associated with PCa metastasis. These results were verified in clinical specimens by real‐time PCR and immunohistochemistry assays. Through methylation analysis, the downregulated expression of UNC5D in PCa tissues and cell lines was found to be attributable to the hypermethylation of the promoter. A negative correlation was observed between methylation and UNC5D mRNA expression in PCa samples. The ectopic expression of UNC5D in PCa cells effectively reduced their ability to migrate and invade both in vitro and in vivo, and siRNA‐mediated knockdown of UNC5D yielded consistent results. UNC5D can recruit and activate death‐associated protein kinase 1, which remained to be essential for its metastatic suppressor function. In conclusion, these results suggested that UNC5D as a novel putative metastatic suppressor gene that is commonly down‐regulated by hypermethylation in PCa. Abstract : Collectively, we have identified that UNC5D as a novel candidate metastasis suppressor that is silenced by promoter hypermethylation in prostate cancer (PCa). We present clinical evidence that UNC5D expression is negatively associated with its methylation level, as well as PCa metastasis. We also validated the metastasis suppressor function of UNC5D in PCa cells, which is dependent on the downstream activation of death‐associated protein kinase 1. Our findings proposed that UNC5D could be a potential diagnostic biomarker and therapeutic target for metastatic PCa.